Vortex fluidic enhanced enzymatic hydrolysis of gelatin from barramundi skin for 3D printing - Xiaoqi Sun; Yixiao Wu; Hao Wang; Shan He; Shan He; Shan He; Shan He; David J. Young; Suresh Thennadil; Colin L. Raston; Mostafa R. Abukhadra; Ahmed M. El-Sherbeeny; et al. (Frontiers in Sustainable Food Systems, 2025)
IntroductionProcessing with a continuous flow thin film vortex fluidic device (VFD) significantly improves the efficiency of enzymatic hydrolysis of barramundi skin gelatin compared with conventional methodology.MethodsDegree of hydrolysis, scanning electron microscopy, rheological properties, texture profile analysis, and dynamic light scattering were applied in this study.Results and discussionThe processing time was reduced from 120 min to 20 min, and the degree of hydrolysis increased from 55.0 to 74.5%. VFD-treated gelatin hydrolysates were combined with starch in different proportions for use as 3D printing inks. The ink composed of 60% starch and 40% fish gelatin hydrolyate gave an ink with a regular crosslinked internal structure, relatively high storage modulus (G’), adhesiveness (399 g.sec) and loss modulus (G”) suitable for 3D printing. This new, one-step processing methodology has the potential to add value to an abundant waste product of the seafood industry.